2009
DOI: 10.1016/j.bcp.2009.04.031
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinic actions on neuronal networks for cognition: General principles and long-term consequences

Abstract: Nicotine enhances cognitive performance in humans and laboratory animals. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(77 citation statements)
references
References 131 publications
(173 reference statements)
2
74
0
1
Order By: Relevance
“…Saxena et al (2011) have shown that a 14-day chronic Nic treatment in icv-STZ-treated animals avoids mitochondrial dysfunctions and caspase-3 activity, evidencing the Nic protective influence against apoptosisrelated processes. Our findings, together with those from Srivareerat et al (2011), are in agreement with multiple reports on Nic neuroprotective roles (Fujii and Sumikawa, 2001;Picciotto and Zoli, 2002;Liu and Zhao, 2004;Unger et al, 2006;Poorthuis et al, 2009). In addition, it has been shown that neuroprotection is blocked by nAChR antagonists (Akaike et al, 2010), and that nicotinic receptors can modulate mnemonic processes involving ACh release and Ca 2+ homeostasis (Se´gue´la et al, 1993;McGehee et al, 1995).…”
Section: Discussionsupporting
confidence: 93%
“…Saxena et al (2011) have shown that a 14-day chronic Nic treatment in icv-STZ-treated animals avoids mitochondrial dysfunctions and caspase-3 activity, evidencing the Nic protective influence against apoptosisrelated processes. Our findings, together with those from Srivareerat et al (2011), are in agreement with multiple reports on Nic neuroprotective roles (Fujii and Sumikawa, 2001;Picciotto and Zoli, 2002;Liu and Zhao, 2004;Unger et al, 2006;Poorthuis et al, 2009). In addition, it has been shown that neuroprotection is blocked by nAChR antagonists (Akaike et al, 2010), and that nicotinic receptors can modulate mnemonic processes involving ACh release and Ca 2+ homeostasis (Se´gue´la et al, 1993;McGehee et al, 1995).…”
Section: Discussionsupporting
confidence: 93%
“…Consequently this feature may alter the PFC's role in the ability to establish a rational evaluation of smoking even during adult age. We also observed that nicotine increased noradrenaline release in the PFC (Carboni et al, 2010) thus suggesting that this increase may have a role in the nicotine enhancement of cognition (see the review of Poorthuis et al, 2009). Furthermore local infusion of nicotine in the prelimbic mPFC can increase mPFC glutamate extracellular concentration supporting the role of nAChRs in modulating thalamocortical input to the PFC (Gioanni et al, 1999).…”
Section: Prefrontal Cortex Dopamine Transmission In Adolescence and Dsupporting
confidence: 61%
“…a4b2 receptors have a very high affinity for nicotine and desensitize at low concentrations of nicotine, corresponding to blood concentrations experienced by smokers. In contrast, a7 receptors have a low affinity for nicotine but do not desensitize at low nicotine concentrations (Poorthuis et al, 2009). In animal studies, local acute and chronic hippocampal infusion of a4b2 antagonists cause significant spatial working memory impairment (Arthur and Levin, 2002), while a4b2 receptor agonists significantly improve working memory and attention function .…”
Section: Introductionmentioning
confidence: 99%